Partitioning and budget of inorganic and organic chlorine species observed by MIPAS-B and TELIS in the Arctic in March 2011 - Wetzel, G.; Oelhaf, H.; Birk, M.; De Lange, A.; Engel, A.; Friedl-Vallon, F.; Kirner, O.; Kleinert, A.; Maucher, G.; Nordmeyer, H.; Orphal, J.; Ruhnke, R.; et al. (Karlsruhe, 2015)
The Arctic winter 2010/11 was characterized by a persisting vortex with extremely cold temperatures in the lower stratosphere above northern Scandinavia leading to a strong activation of chlorine compounds (ClOx) like Cl, Cl2, ClO, ClOOCl, OClO, and HOCl which rapidly destroyed ozone when sunlight returned after winter solstice. MIPAS (Michelson Interferometer for Passive Atmospheric Sounding) and TELIS (Terahertz and submillimeter Limb Sounder) balloon measurements obtained in northern Sweden on 31 March 2011 inside the polar vortex have provided vertical profiles of inorganic and organic chlorine species as well as diurnal variations of ClO around sunrise over the whole altitude range in which chlorine is undergoing activation and deactivation. This flight was performed at the end of the winter during the last phase of ClOx deactivation. The complete inorganic and organic chlorine partitioning and budget in the stratosphere has been derived by combining MIPAS-B and TELIS simultaneously observed molecules. A total chlorine amount of 3.41 ± 0.30 ppbv is inferred from the measurements. This value is in line with previously carried out stratospheric observations confirming the slightly decreasing chlorine trend in the stratosphere. Observations are compared and discussed with the output of a multi-year simulation performed with the Chemistry Climate Model EMAC (ECHAM5/MESSy Atmospheric Chemistry). The simulated stratospheric total chlorine amount is in accordance with the MIPAS-B/TELIS observation taking into account the fact that some chlorine source gases and very short lived species are not included in the model.